How Hip Hop Became Hit Pop Radio, Rap, and Race - Coddington, Amy (University of California Press, 2023)
How Hip Hop Became Hit Pop examines the programming practices at commercial radio stations in the 1980s and early 1990s to uncover how the radio industry facilitated hip hop's introduction into the musical mainstream. Constructed primarily by the Top 40 radio format, the musical mainstream featured mostly white artists for mostly white audiences. With the introduction of hip hop to these programs, the radio industry was fundamentally altered, as stations struggled to incorporate the genre's diverse audience. At the same time, as artists negotiated expanding audiences and industry pressure to make songs fit within the confines of radio formats, the sound of hip hop changed. Drawing from archival research, Amy Coddington shows how the racial structuring of the radio industry influenced the way hip hop was sold to the American public, and how the genre's growing popularity transformed ideas about who constitutes the mainstream. "Here it is-bam! The definitive story of rap, race, radio, and marketplace during hip hop's Golden Age. Amy Coddington combines an archivist's rigor and a raconteur's wit in documenting what those of us of a certain age remember but, perhaps, never fully grasped: how, amidst expanding racial inequalities and against all odds, rap music became the most popular genre in America." - Anthony Kwame Harrison, author of Hip Hop Underground: The Integrity and Ethics of Racial Identification "Making use of trade publications that have received little scholarly attention, Coddington has crafted a provocative and lucid alternative history that tracks how the radio industry's engagement with hip hop in the 1980s and 1990s both reflected and shaped changing ideas about race and music." - Loren Kajikawa, author of Sounding Race in Rap Songs